2023
DOI: 10.1038/s41419-023-06161-9
|View full text |Cite
|
Sign up to set email alerts
|

The oleic/palmitic acid imbalance in exosomes isolated from NAFLD patients induces necroptosis of liver cells via the elongase-6/RIP-1 pathway

Maria Principia Scavo,
Roberto Negro,
Valentina Arrè
et al.

Abstract: Excessive toxic lipid accumulation in hepatocytes underlies the development of non-alcoholic fatty liver disease (NAFLD), phenotypically characterized by necrosis and steato-fibrosis, whose molecular mechanism is not yet fully understood. Patients with NAFLD display an imbalanced palmitic (PA) to oleic acid (OA) ratio. Moreover, increasing experimental evidence points out a relevant involvement of the exosomal content in disease progression. Aim of the study was to highlight the PA/OA imbalance within circulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…When the exosomes carry a higher concentration of palmitic acid compared to oleic acid, the hepatic cells that endocytose these vesicles activate the necroptosis pathway, leading to cell death. Conversely, restoring the balance of these two acids in exosomes from MASLD patients prevents cell death [ 44 ]. Therefore, the use of a lipidomic analysis of plasma-derived exosomes could be a good diagnostic and prognostic approach in patients with MASLD.…”
Section: Evs As Mediators In Gastroenteric Pathogenesis and Biomarker...mentioning
confidence: 99%
See 2 more Smart Citations
“…When the exosomes carry a higher concentration of palmitic acid compared to oleic acid, the hepatic cells that endocytose these vesicles activate the necroptosis pathway, leading to cell death. Conversely, restoring the balance of these two acids in exosomes from MASLD patients prevents cell death [ 44 ]. Therefore, the use of a lipidomic analysis of plasma-derived exosomes could be a good diagnostic and prognostic approach in patients with MASLD.…”
Section: Evs As Mediators In Gastroenteric Pathogenesis and Biomarker...mentioning
confidence: 99%
“…These modifications in exosomal membranes influence the membranes of stellate cells (LX2) stimulated by the exosomes from these patients. This suggests a potential role in the early detection of disease progression, which could be discerned through the lipidomic analysis of exosomal membranes [ 44 , 45 ]. In the realm of liver pathologies, the analysis of circulating EVs has proven effective in distinguishing patients with metabolic dysfunction-associated steatohepatitis (MASH) from those with chronic hepatitis compared to healthy controls.…”
Section: Evs As Mediators In Gastroenteric Pathogenesis and Biomarker...mentioning
confidence: 99%
See 1 more Smart Citation
“…The erythrocyte membrane might be a valid biomarker for the fatty acid composition present in other body cells. Several studies have shown that changes in the fatty acid composition of red blood cell (RBC) membranes have been observed in different metabolic diseases, including Nonalcoholic Fatty Liver Disease (NAFLD) and colorectal cancer (CRC) [ 7 , 8 , 9 , 10 ]. In this regard, we have previously found low levels of Saturation Index, given by the relationship of stearic acid to oleic acid in RBC membranes of patients with severe Nonalcoholic Fatty Liver Disease (NAFLD) compared to controls [ 11 ].…”
Section: Introductionmentioning
confidence: 99%